Sistem E-Commerce untuk Meningkatkan Penjualan Alat Elektronik Menggunakan Metode Extreme Programming - Suherman, Muhammad Ilham; Maryani, Desi; Amir, Ilmawati; Angraeni, Reny (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2024)
This study aims to develop and implement an efficient and effective e-commerce-based electronic goods sales system using the Extreme Programming (XP) system development method. The main focus of this research is to enhance the promotion and sales processes in small and medium-sized stores to be competitive in the digital era. XP was chosen due to its iterative and incremental approach and customer involvement at every stage of software development to ensure the final product meets user needs and expectations. The results indicate that the developed system can expand customer reach and improve the operational efficiency of these stores.